Action research into the student use of computer-based spaced-repetition vocabulary learning within a Thai Primary English program - Whitsed, David (2015)
The focus of this action research study was the factors influencing participation of young ESL students using spaced-repetition computer software. Sixty-two Thai primary school students from the ages eight to eleven were involved. They were trained in the use of Anki which provided them with questions and answers based on their weekly English vocabulary list. The software was used at home on a voluntary basis. Questionnaires and focus groups using stimulated recall were employed to identify key factors influencing use in the third week. Regular use was achieved when perceived positive learning benefits, enjoyment and rewards outweighed demands on students’ free time. However, forty six students indicated that these benefits were insufficient to encourage use of more than three days a week. The principal conclusion was that learning benefits should be optimised through a tailoring of the language recall task to students’ abilities, but that the software would not be adopted effectively by the majority of users on a voluntary basis.